Highly absorptive dressing composed of natural latex loaded with alginate for exudate control and healing of diabetic wounds - Barros, Natan Roberto [UNESP]; Ahadian, Samad; Tebon, Peyton; Rudge, Marilza Vieira Cunha [UNESP]; Barbosa, Angélica Mércia Pascon [UNESP]; Herculano, Rondinelli Donizetti [UNESP] (Elsevier, 2021)
Wounds can take longer to heal in diabetic patients, increasing the risk of infections and other complications. The most common wounds in diabetic patients are diabetic foot ulcers, a severe complication associated with diabetes mellitus. The United States alone spends $18.7 billion annually on care for these wounds including pain and infection management. If improperly managed, infected lesions may require amputation. The enormous cost associated with wound care and the dire consequences if not cared for properly, emphasize the need to develop strategies to accelerate the healing of diabetic foot wounds. Natural rubber latex (NRL), extracted from Hevea brasiliensis (the rubber tree), has been widely applied as a carrier system for several pharmacologically active compounds. Furthermore, it has been shown to encourage angiogenesis, facilitate cell adhesion, and accelerate wound healing. When NRL dressings are applied to wounds of diabetic patients, exudate release is upregulated. The production of exudate is essential to wound healing as it provides the nutrients, proteins, cells, and environment required for regeneration. Despite its benefits, it is necessary to control excess exudate to avoid prolonged healing resulting from dermatitis, maceration of the wound edges, and lesion growth. In order to solve the problem of excessive exudate release induced by NRL membrane application, we aimed to regulate humidity by absorbing excess exudate and increase water vapor transmission. We developed a highly absorptive, permeable, alginate loaded NRL dressing. Adding alginate to NRL membranes, swelling was increased up to 80-fold, absorbing 4.80 g of water per gram of dry membrane. Moreover, water vapor transmission was improved drastically as the material transmitted 480% more water vapor than pure NRL membranes. Furthermore, in vitro tests demonstrated not only that the membranes are biocompatible, but that they also enhance cell proliferation. Through a cell proliferation assay, we observed that fibroblast proliferation was improved by the presence of NRL while the keratinocytes benefit from the presence of alginate. The NRL-alginate dressings have great potential to improve diabetic wound care by accelerating the healing process.
Keywords: Alginate; Biomaterial; Cell proliferation; Exudate; Natural rubber latex; Wound healing